Empire of the air : the men who made radio - Lewis, Tom, 1942- (Cornell University Press, 2021)
"Biography of 3 Americans, Lee de Forest, Howard Armstrong, and David Sarnoff, who turned a hobbyists' toy into radio, and launch the modern communications age. The narrative of their creations is punctuated by acts of idealism and imagination, greed and envy, ambition and determination--and genius. It covers 1899 to 1954"-- Provided by publisher.
Keywords: De Forest, Lee, -- 1873-1961.; Armstrong, Edwin H. -- (Edwin Howard), -- 1890-1954.; Sarnoff, David, -- 1891-1971.; Armstrong, Edwin H. -- (Edwin Howard), -- 1890-1954; De Forest, Lee, -- 1873-1961; Sarnoff, David, -- 1891-1971; Radio -- United States -- History.; Radio -- United States -- Biography.; TECHNOLOGY & ENGINEERING / Radio; Radio; United States; Biography; Biographies; History; Biographies.